Iron Status in Febrile Seizure: A Case-Control Study - SALEHI OMRAN, M.R.; TAMADDONI, A.; NASEHI, MM.; BABAZADEH, H.; ALIZADEH NAVAEI, R. (Iranian Journal of Child Neurology, 2009)
Objective Data on the relationship between iron deficiency anemia and febrile convulsions are controversial. The aim of this study was to determine the association between iron deficiency anemia and febrile convulsions among children. Materials & Methods This case-control study was conducted during 2006-2007, on 90 children with febrile seizures (case) and 90 febrile children without seizures (control) referred to the Amirkola children hospital (a referral hospital in the north of Iran). Two groups were matched for age and sex. In all children hemoglobin (Hb) level, hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and plasma ferritin (PF) were determined and the data collected were analyzed statistically using the t-test. Results The mean PF and TIBC levels were not significantly different in the febrile seizure compared to the reference group; neither were differences in Hb levels statistically significant between two groups. However MCV and MCH were significantly higher in the febrile seizure group (p Conclusion Plasma ferritin levels were not significantly lower in children with febrile seizures in comparison with the children in control group. It seems that iron insufficiency does not play a role in pediatric febrile seizures.